Effect of sodium 4-phenylbutyrate on clenbuterol-mediated muscle growth - Brown, David M.; Jones, Sarah; Daniel, Zoe C.T.R.; Brearley, Madelaine C.; Lewis, Jo E.; Ebling, Francis J.P.; Parr, Tim; Brameld, John M. (Public Library of Science, 2018)
Previously, we highlighted induction of an integrated stress response (ISR) gene program in skeletal muscle of pigs treated with a beta-adrenergic agonist. Hence we tested the hypothesis that the ER-stress inhibitor, sodium 4-phenylbutyrate (PBA), would inhibit Clenbuterol-mediated muscle growth and reduce expression of genes that are known indicators of an ISR in mice. Clenbuterol (1mg/kg/day) administered to C57BL6/J mice for 21 days increased body weight (p<0.001), muscle weights (p<0.01), and muscle fibre diameters (p<0.05). Co-administration of PBA (100mg/kg/day) did not alter the Clenbuterol-mediated phenotype, nor did PBA alone have any effects compared to that of the vehicle treated mice. Clenbuterol increased skeletal muscle mRNA expression of phosphoserine amino transferase 1 (PSAT1, p<0.001) and cyclophillin A (p<0.01) at day 3, but not day 7. Clenbuterol decreased mRNA expression of activating transcription factor (ATF) 4 and ATF5 at day 3 (p<0.05) and day 7 (p<0.01), X-box binding protein 1 (XBP1) variant 2 mRNA at day 3 only (p<0.01) and DNA damage inducible transcript 3 (DDIT3/CHOP) mRNA at day 7 only (p<0.05). Co-administration of PBA had no effect on Clenbuterol-induced changes in skeletal muscle gene expression. In contrast, treatment of C2C12 myotubes with 5mM PBA (8hr) attenuated the thapsigargin-induced ISR gene program. Prolonged (24-48hr) treatment with PBA caused atrophy (p<0.01), reduced neoprotein synthesis (p<0.0001) and decreased expression of myogenin and fast myosin heavy chain genes (p<0.01), indicating an inhibition of myogenic differentiation. In summary, Clenbuterol did not induce an ISR gene program in mouse muscle. On the contrary, it reduced expression of a number of ISR genes, but it increased expression of PSAT1 mRNA. Co-administration of PBA had no effect on Clenbuterol-mediated muscle growth or gene expression in mice, whereas PBA did inhibit thapsigargin-induced ISR gene expression in cultured C2C12 cells and appeared to inhibit myogenic differentiation, independent of altering ISR gene expression.